Airlines´ work with pricing and relationship management in belly cargo operations - Austrheim, Sondre; Dagander, Niklas (My University, 2015)
Airlines sell cargo space in the belly of their airplanes to earn extra revenue on passenger flights. Because the airplanes will fly with or without this cargo, belly cargo can be characterized as a by-product of passenger aviation. Pricing and relationship management are important factors in the area of marketing for most companies. There are many different pricing strategies to choose from to maximize profit on a service. Relationships with customer and suppliers can have many different features, depending on the situation. This thesis investigates how airlines work with pricing strategies and relationship management in their belly cargo business. A qualitative method has been used to produce a thorough analyse of the airlines’ work. Both primary data, in the form of interviews, and secondary data, in the form of relevant theory, are analysed in this thesis. The four interviews are all with European airlines that have chosen to be anonymous. The results show that the airlines work in different ways with pricing and relationship management. Three airlines work with cost plus based pricing while a fourth airline claims that it uses a competition based pricing strategy. The complexity of the airlines’ relationships is not the same. Some claim that their relationships are complex with a high need of information exchange and one airline claims that it has no complex relationships. None of the airlines have a relationship manager in their organization, but its tasks are included in the other employees’ work.
Keywords: Transportteknik och logistik; Transport; Transport Systems and Logistics; Transport